5-Aminolevulinic Acid Photodynamic Therapy Combined with Intralesional Triamcinolone and 5-Fluorouracil to Treat Acne Hypertrophic Scar - Wei J; Du L; Cao Z; Li M; Zhang C; Zhang C; Meng L (Dove Medical Press, 2023)
Jingjing Wei, Lingyun Du, Zhiqiang Cao, Mingming Li, Chunhong Zhang, Chunmin Zhang, Liya Meng Department of Dermato-Venereology, The Second Hospital of Shandong University, Jinan, People's Republic of ChinaCorrespondence: Liya Meng, Department of Dermato-venereology, The Second Hospital of Shandong University, 247 Beiyuan Dajie Street, Jinan, 250033, People's Republic of China, Tel +86-531-85875027, Fax +86-531-88962544, Email mly0706@sina.comBackground: Acne is a chronic inflammatory disease of the pilosebaceous unit. Improper treatment of acne can lead to skin lesions in some people. Acne hypertrophic scar is relatively rare, but it significantly affects the appearance and beauty, and usually has a great psychological and social impact on patients.Objective: To evaluate the clinical efficacy and safety of 5-aminolevulinic acid photodynamic therapy (ALA-PDT) combined with 5-fluorouracil (5-FU) injection and triamcinolone acetonide (TAC) solution in the treatment of acne hypertrophic scars.Methods: This article included 13 outpatients with acne accompanied by acne hypertrophic scar who were treated from September 2018 to September 2022. All patients received ALA-PDT combined with intralesional injection of 5-FU and TAC. At first, patients received ALA-PDT once every two weeks. After the third ALA-PDT, 5-FU and TAC were mixed in a ratio of 3:7, and then immediately injected in the local scars. The effect was observed after 1 month. If the effect is not obvious, a further injection of 5-FU and TAC to the lesion is necessary. The patients were followed up for 6 months. The Vancouver Scars Scale (VSS) was used to evaluate the efficacy before and after treatment and photos of patients were collected.Results: After ALA-PDT combined with intralesional 5-FU and TAC, all patients achieved good clinical efficacy. 23.08% of patients received one local injection and 76.92% received two local injections. After treatment, the scar lesions were reduced and flattened, and the scars became soft. The total score of VSS after treatment was significantly lower than before, and the difference was statistically significant (P< 0.05). The main adverse reactions were pain, erythema, and pigmentation, which can subside within 3 weeks. There was no recurrence after 6 months of follow-up.Conclusion: ALA-PDT combined with intralesional injection of 5-FU and TAC significantly affects acne hypertrophic scars, which is worthy of further in-depth and large-scale research.Keywords: acne hypertrophic scars, ALA-PDT, 5-FU, TAC, acne